Comparative transcriptome analysis of emerging young and mature leaves of Bienertia sinuspersici, a single-cell C4 plant - Sharpe,Richard M.; Hewitt,Seanna; Edwards,Gerald; Dhingra,Amit (PeerJ, 2025)
Background Efficient carbon capture by plants is crucial to meet the increasing demands for food, fiber, feed, and fuel worldwide. One potential strategy to improve the photosynthetic performance of plants is the conversion of C3-type crops to C4-type crops, enabling them to perform photosynthesis at higher temperatures and with less water. C4-type crops, such as corn, possess a distinct Kranz anatomy, where photosynthesis occurs in two distinct cell types. Remarkably, Bienertia sinuspersici is one of the four known land plant species that perform C4 photosynthesis within a single cell. This unique single-cell C4 (SCC4) anatomy is characterized by dimorphic chloroplasts and corresponding intracellular biochemistry. Because young, emergent Bienertia leaves first exhibit C3anatomy and then differentiate into the C4 anatomy as the leaves mature, Bienertia represents an excellent system to explore the basis for a C3 to C4 transition. Methods To gain insight into the genes and pathways associated with the C3 to C4 transition between emerging young and mature Bienertia sinuspersici leaves, a comparative transcriptome analysis was conducted in which global gene expression and gene ontologies were compared between the two stages. Results In the emergent leaf, differentially expressed genes and enrichment of ontologies associated with the cell cycle and cytoskeletal dynamics were observed, while the mature leaf displayed enrichment of processes associated with photosynthesis and cellular energetics. Additionally, numerous transcription factors (TFs) associated with metabolic homeostasis, hormone and stress signaling, and developmental regulation were expressed throughout development, with unique TF expression profiles at each stage. These data expand our insights into the molecular basis of Binertia’s unique cellular compartmentalization, chloroplast dimorphism, and single-cell C4 biochemistry and provide information that will be useful in the ongoing efforts to transform C3-type crops into C4 type.
Keywords: Photosynthesis; Single-cell C4 plant; Gene expression; Developmental transcriptomics; Chenopodiaceae